The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1063/1.1562739
|View full text |Cite
|
Sign up to set email alerts
|

Electronic line-up in light-emitting diodes with alkali-halide/metal cathodes

Abstract: The electronic nature of metal-semiconductor contacts is a fundamental issue in the understanding of semiconductor device physics, because such contacts control charge injection, and therefore play a major role in determining the electron/hole population in the semiconductor itself. This role is particularly important for organic semiconductors as they are generally used in their pristine, undoped form. Here, we review our progress in the understanding of the energy level line-up in finished, blue-emitting, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
114
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(118 citation statements)
references
References 93 publications
3
114
1
Order By: Relevance
“…[76,121] Several groups have made efforts regarding the construction of a band diagram, based on indirect evidence, such as transient photocurrent [171] and surface potential characterization. [180] On the other hand, electroabsorption spectroscopy [185,186] has proven to be a powerful approach to study the internal electric field and to characterize the interfacial barrier modulation under working conditions. [187] Li et al [115] found that there is a shift of the built-in potential during the device scanning.…”
Section: Modulation Of the Energetic Environment At Interfacesmentioning
confidence: 99%
“…[76,121] Several groups have made efforts regarding the construction of a band diagram, based on indirect evidence, such as transient photocurrent [171] and surface potential characterization. [180] On the other hand, electroabsorption spectroscopy [185,186] has proven to be a powerful approach to study the internal electric field and to characterize the interfacial barrier modulation under working conditions. [187] Li et al [115] found that there is a shift of the built-in potential during the device scanning.…”
Section: Modulation Of the Energetic Environment At Interfacesmentioning
confidence: 99%
“…8,19) The use of both LiF and PEDOT-PSS in this way has proven effective in photovoltaic cells 20) and polymer light emitting diodes. 21,22) In fact, the use of alkali halide sandwich layers to improve injection at the cathode electrode has been used successfully in a wide variety of organic electronic devices, e.g., refs. 21, 23-26. In this work the cathode side is studied, particularly the beneficial effect that the LiF layer has on the interface between the Al and the active organic layer.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the insertion of an inorganic or organic electron injection layer ͑EIL͒/transport layer between the cathode and emissive layer can provide an intermediate step for facilitating electron injection. [10][11][12] One example is the use of lithium fluoride ͑LiF͒. When incorporated into polymer light-emitting diodes ͑PLEDs͒, the LiF layer improves the device performance by increasing the electron attenuation length, by suppressing the interfacial reactions of the metal electrode with emissive layer during the cathode evaporation, and/or by reducing the barrier height of the electron injection through formation of a low work function interfacial layer at the cathode.…”
mentioning
confidence: 99%
“…When incorporated into polymer light-emitting diodes ͑PLEDs͒, the LiF layer improves the device performance by increasing the electron attenuation length, by suppressing the interfacial reactions of the metal electrode with emissive layer during the cathode evaporation, and/or by reducing the barrier height of the electron injection through formation of a low work function interfacial layer at the cathode. 10,[13][14][15] The recent research using cationic systems [16][17][18] implies that anionic conjugated polyelectrolytes might offer several interesting opportunities for use in polymer-based optoelectronic devices. In light-emitting electrochemical cells ͑LECs͒, the mobile ions enable redox doping and the formation of ohmic contacts.…”
mentioning
confidence: 99%